Operating Results of Department and Specialty Stores in 1947 (Book). - Smith, Frank P.; Dickman, A. B. (The Accounting Review, 1949)
Reviews the book "Operating Results of Department and Specialty Stores in 1947," by Malcolm P. McNair.